Individuals with Attention-Deficit Hyperactivity Disorder in a Multimedia Learning Environment - Król-Gierat, Werona (Wydział Neofilologii UAM w Poznaniu i Wydział Lingwistyki Stosowanej UW, 2014)
The paper is aimed at investigating the functioning of individuals with Attention-Deficit Hyperactivity Disorder (ADHD) in a multimedia learning environment. The first part defines the disorder, focusing on brain processes of ADHD individuals. The second part discusses key theories connected with multimedia learning. Finally, the last part is an attempt to observe how ADHD learners learn from words and pictures.
Keywords: Attention-Deficit Hyperactivity Disorder (ADHD); Cognitive Load Theory (CLT); Multimedia Learning; Special Educational Needs (SPE); brain research